Arab Keturunan di Indonesia; Tinjauan Sosio-Historis tentang Arab Keturunan dan Perannya dalam Kehidupan Masyarakat Indonesia - Yahya, Yahya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2002)
The role of Arabic-Indonesian community in Islamic da 'wah in Indonesia is quite important. However, there are few studies of their role that have been conducted It is for this reason that the writer would like to observe the role and the existence of this community from the social-historical perspective. There are two theories in understanding their relationship with indigenous people. The first is identical theory which perceives that historically Islam is identical with Arab and therefore cannot be separated from Arabic people. The second theory is that the arrival and the development of Arabic community in Indonesia, on the perspective of anthropological history, is closely related to the history of conversion to Islam and the development of Islam in society. The writer tries to observe their social life and their active role in the development of Indonesian society.